2011
DOI: 10.1007/s11164-011-0422-8
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for the preparation of cyclic polyarenes based on single electron transfer-promoted photocyclization reactions

Abstract: Single electron transfer (SET)-promoted photocyclization reactions of substrates comprised of benzylsilane tethered to phthalimides were subjected to an exploratory study in order to probe a new approach for the preparation of cyclic polyarenes. The results show that UV irradiation of the substrates leads to efficient photochemical reactions that are initiated by SET from benzylsilane moieties to the excited phthalimide acceptor. Ensuing desilylation reactions of the benzylsilane cation radical moieties in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…65 Scheme 66 Photochemical generation of medium-and large-ring heterocycles from imides Park has prepared macrocyclic N-heterocycles by irradiation of phthalimides bearing a polyether substituent on the nitrogen. 66 As shown in Scheme 68, the starting polyether imide underwent photo-induced SET on the phthalimide moiety and loss of Me 3 Si radical to generate the corresponding biradical. Loss of the SiMe 3 group gave the terminal biradical 35, which cyclized to 36.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…65 Scheme 66 Photochemical generation of medium-and large-ring heterocycles from imides Park has prepared macrocyclic N-heterocycles by irradiation of phthalimides bearing a polyether substituent on the nitrogen. 66 As shown in Scheme 68, the starting polyether imide underwent photo-induced SET on the phthalimide moiety and loss of Me 3 Si radical to generate the corresponding biradical. Loss of the SiMe 3 group gave the terminal biradical 35, which cyclized to 36.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…In early studies, we also demonstrated that SET-promoted photochemical addition and cyclization reactions of a number of α-trialkylsilyl substituted electron donors, including allyl- and benzyl-silanes as well as silyl-ethers, -thioethers, and -amides, ,, take place regioselectively and efficiently and that these processes can be applied to the synthesis of interesting target molecules. ,, Owing to the growing importance of the need for functionalized fullerenes in current strategies employed to design photovoltaic devices, we have initiated a broad program to explore SET photoaddition reactions of a variety of α-trialkylsilyl-substituted electron donors to fullerenes with the aim of evaluating the scope and efficiency of the processes. In the initial phase of this long-range study, we explored photoaddition reactions of C 60 with α-silyl tertiary amines.…”
Section: Introductionmentioning
confidence: 99%